Cancer targeting with biomolecules: a comparative study of photodynamic therapy efficacy using antibody or lectin conjugated phthalocyanine-PEG gold nanoparticles. Issue 4 (21st January 2015) - Obaid, Girgis; Chambrier, Isabelle; Cook, Michael J.; Russell, David A.
Abstract : The functionalisation of therapeutic nanoparticle constructs with cancer-specific biomolecules can enable selective tumour accumulation and targeted treatment. Abstract : The functionalisation of therapeutic nanoparticle constructs with cancer-specific biomolecules can enable selective tumour accumulation and targeted treatment. Water soluble gold nanoparticles ( ca. 4 nm) stabilised by a mixed monolayer of a hydrophobic zinc phthalocyanine photosensitiser (C11Pc) and hydrophilic polyethylene glycol (PEG) have been prepared. The C11Pc-PEG gold nanoparticle constructs were further functionalised with jacalin, a lectin specific for the cancer-associated Thomsen–Friedenreich (T) carbohydrate antigen, or with monoclonal antibodies specific for the human epidermal growth factor receptor-2 (HER-2). The two biofunctionalised nanoparticle conjugates produced similar levels of singlet oxygen upon irradiation at 633 nm. Importantly, both nanoparticle conjugates demonstrated extensive, yet comparable, phototoxicity in HT-29 colorectal adenocarcinoma cells (80–90%) and in SK-BR-3 breast adenocarcinoma cells (>99%). Non-conjugated C11Pc-PEG gold nanoparticles were only minimally phototoxic. Lysosomal colocalisation studies performed with the HT-29 colon cancer cells and the SK-BR-3 breast cancer cells revealed that both nanoparticle conjugates were partially localised within acidic organelles, which is typical of receptor-mediated endocytosis. The similarity of the targeted PDT efficacy of the two biofunctionalised C11Pc-PEG gold nanoparticles is discussed with respect to targeting ligand binding affinity and cell surface antigen density as key determinants of targeting efficiency. This study highlights how targeting small cell-surface molecules, such as the T antigen, can mediate a selective photodynamic treatment response which is similar to that achieved when targeting overexpressed protein receptors, such as HER-2. The high prevalence of the T antigen present on the cellular surface of primary tumours emphasises the broad potential applications for lectin-targeted therapies.